A Study On Teachers' Resolution Of Children's Conflict Events In Regional Activities - Li huixia (Pacific International Journal, 2022)
This study begins with the phenomenon of conflict in young children's regional activities. Through an investigation of teachers' resolution of conflict events among young children in zone activities, the current situation of teachers' response to conflict in young children's zone activities was analyzed in two dimensions: teachers' response style and timing of intervention. After data analysis and research, this study concluded that there were three problems: teachers' teaching philosophy was flawed, teachers' handling of conflict events was arbitrary, and teachers' timing of intervention in conflict was inappropriate. Combined with related teaching theories, this study suggests that teachers should improve their educational concepts and optimize the way they handle conflict events; give full play to young children's subjectivity, avoid controlling children, and grasp the timing of intervention to guide young children properly.